Interleukin 6 inhibits mouse placental lactogen II but not mouse placental lactogen I secretion in vitro. - Yamaguchi, M (1993)
The mouse placenta produces several polypeptides belonging to the prolactin-growth hormone gene family, including mouse placental lactogen (mPL) I and mPL-II. The present study was undertaken to determine whether the secretion of mPL-I and mPL-II is regulated by interleukin 6 (IL-6), which is present in the placenta and has previously been reported to stimulate the secretion of pituitary members of this gene family. Effects of human and mouse IL-6 on mPL-I and mPL-II secretion were examined in primary cultures of placental cells from days 7, 9, and 12 of pregnancy. IL-6 caused a dose-dependent reduction in the mPL-II concentration in the medium of cells from days 9 and 12 of pregnancy but did not affect the mPL-II concentration in the medium of cells from day 7 of pregnancy or the mPL-I concentration in the medium of cells from days 7 or 9 of pregnancy. The lowest concentration of human IL-6 that significantly inhibited mPL-II secretion was 250 pM. The effect of IL-6 on the mPL-II concentration in the medium was due primarily to inhibition of mPL-II synthesis, which resulted at least partly from a decrease in the steady-state level of mPL-II mRNA. These data raise the possibility that IL-6 may regulate mPL-II production after midpregnancy in vivo.